Pendampingan “Maggot BSF” Pengolahan Sampah dan Sarana Wisata Edukasi Karang Taruna Desa Bawuran Pleret Bantul - Yulianto, Prafidhya Dwi; Novitasari, Dwi; Prasetyo, Agung Slamet; Ambarwati, Lilik (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
Cultivating BSF maggots can be used to decompose organic waste. This community service activity aims to: (1) find out the amount and sorting of organic waste produced by Bawuran village residents; (2) Bawuran village residents have a special place for organic waste and organic waste sorting; (3) Bawuran village Youth Organization is able to cultivate BSF maggots; (4) Bawuran village Youth Organization is able to utilize the results of BSF Maggot cultivation; (5) The government/residents of Bawuran village have a waste education tourist attraction. The method of implementing community service activities is by means of training and mentoring. As a result of this community service activity, the residents of Bawuran village have a waste sorting place, Karang Taruna is able to cultivate BSF maggots and there is a waste education tour in Puncak Sosok. This community service activity provides waste processing solutions, community empowerment and adds economic value to community income by utilizing waste cultivation products and educational tourism.